2020
DOI: 10.1097/tp.0000000000002931
|View full text |Cite
|
Sign up to set email alerts
|

Recipient Comorbidity and Survival Outcomes After Kidney Transplantation: A UK-wide Prospective Cohort Study

Abstract: Table S1. Comorbidity variable definitions Comorbidity Definition (presence of any of the following) Diabetes • Any cause of diabetes • Type I diabetes -Insulin required from time of diagnosis • Type II diabetes -Treatment with diet-control, oral antidiabetic medication or insulin Ischaemic heart disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…In kidney transplant patients, CVD-related mortality is 2 times higher than the general population since non-classical risk factors such as proteinuria and decreased Glomerular filtration rate (GFR) is more common in addition to DM, HT, HL, which are the classical risk factors for CVD (3). Wu et al (12) found a 2-year patient survival rate of 94.7%, and HF and DM were found as independent risk factors for transplant failure (considered as graft loss and/or patient death). Fuggle et al (13) showed in their reports that come from the United Kingdom (UK), 1st-year survival after LKDT was found to be 99%.…”
Section: Discussionmentioning
confidence: 99%
“…In kidney transplant patients, CVD-related mortality is 2 times higher than the general population since non-classical risk factors such as proteinuria and decreased Glomerular filtration rate (GFR) is more common in addition to DM, HT, HL, which are the classical risk factors for CVD (3). Wu et al (12) found a 2-year patient survival rate of 94.7%, and HF and DM were found as independent risk factors for transplant failure (considered as graft loss and/or patient death). Fuggle et al (13) showed in their reports that come from the United Kingdom (UK), 1st-year survival after LKDT was found to be 99%.…”
Section: Discussionmentioning
confidence: 99%
“…� Frailty: Harhay et al 30 This review of the OPTN data revealed that DDKT recipients with �10% pretransplant weight loss are at increased risk for longer hospital length of stay, higher all-cause graft loss, and higher mortality. � Risk stratification: Wu et al 40 In this prospective cohort study of 2100 KT recipients, peripheral vascular disease, obesity, heart failure, cerebrovascular disease, and chronic liver disease were risk factors for graft loss and mortality in DDKT recipients. For LDKT recipients, heart failure and diabetes were risk factors for poorer transplant survival.…”
Section: Kidney Transplantation (Kt)mentioning
confidence: 99%
“…Wu et al performed a large prospective cohort study of 2100 DDKT and LDKT recipients and analyzed data on 15 comorbidities at the time of transplantation and their relationships with 2-year graft and patient survival. 40 They found that for DDKT recipients, peripheral vascular disease ( 40 Abrol et al sought to identify preoperative factors predicting KT recipients' early admission (within 30 days) to the intensive care unit (ICU). Of the 1527 eligible patients, 305 (20%) required early ICU admission.…”
Section: Other Comorbidities As Risk Factorsmentioning
confidence: 99%
“…However, its identification in transplant patients is essential because of the known adverse relationship between peripheral vascular disease and transplant outcomes. Lower extremity peripheral arterial disease is associated with lower patient survival after renal transplantation, and moderate-to-severe lower extremity arterial calcification is associated with increased waitlist mortality and lower patient and graft survival after transplantation [ 4 , 8 , 9 ]. Peripheral vascular disease is also one of the core parameters utilized in preoperative risk stratification indexes for mortality prediction in transplant candidates [ 10 ].…”
Section: Introductionmentioning
confidence: 99%